Coordinated passivation control for nonlinear power systems based on switching strategy with input constraints. (9th December 2021) - Li, Jian; Zhao, Zhengnan; Wang, Gong; Su, Qingyu
Summary: This article proposed a coordinated passivation control strategy with generator excitation, steam valve, and thyristor‐controlled series compensation to improve the stability of the power system. The d ‐axis reactance and damping coefficients of the system are regarded as uncertain parameters, and the disturbances are also considered when selecting the model. First, under the condition that the control input is constrained, the system with main steam valve control and the fast steam valve is considered as two subsystems by introducing a switched strategy. Then, the disturbance attenuation controller of thyristor‐controlled series compensation is designed by an improved backstepping method, which can enhance the internal and external disturbance attenuation and get a better convergence rate. And the adaptive law of d ‐axis reactance, damping coefficients are obtained at the same time. Next, the control input of two subsystems and generator excitation are designed via the coordinated passivation method. Finally, the effectiveness of the proposed control method is demonstrated by the simulation of a single machine infinite bus system. Abstract : A SMIB system with excitation control, steam valve control, and TCSC control.